In vitro propagation of the Chinese traditional and medicinal plant Heracleum scabridum Franch - Zou, Li-Juan; Hu, Jin-Yao; Luo, Ming-Hua; Wu, Qing-Gui (Bangladesh Journal of Botany, 2019)
Three explants such as stem tips, leaves and petioles of Heracleum scabridum were compared for their shoot development/differentiation ability by using different plant growth regulators (PGRs). The most effective PGRs combination for callus induction and organogenesis was determined. TDZ, Kn, Zn and IAA were used to induce multiple shoots. For indirect organogenesis (from the calli), the best response (27.25 ± 4.19 shoot per stem tips) and (18.23 ± 2.12 per leaves) were obtained in Murashige and Skoog (MS) medium fortified with 0.5 mg/l IAA and 3.0 mg/l Zn with 100, 97.3% induction rate, respectively. MS medium containing 0.5 mg/l IAA and 3.0 mg/l Zn was also found to be optimal for shoot regeneration from petioles. The highest percentage of regeneration (94.6) with mean number of shoots 17.83 ± 4.87 from petioles were produced. For direct organogenesis (from axillary bud shoot clumps), 0.1 mg/l IAA and 1.5 mg/l TDZ were found to be optimal for shoot regeneration of stem tips, with mean numbers of axillary bud shoot clumps 7.12 ± 1.23 were produced. Plantlets were transferred to soil with 95% of plants acclimatized recovered successfully.